Pengukuran Tingkat Kematangan Layanan IT Dengan CMMI - Desi Arisandy; Rudi Rudi; Salsalina Br Sembiring (Jurnal SIFO Mikroskil, 2019)
The use of information technology in an organization's business processes does not guarantee that the organization has been able to provide good IT services. This service needs to be measured from the level of maturity. Capability Maturity Model Integration (CMMI) is a framework that can be used to measure the maturity level or intended maturity level. Accurate measurements certainly depend on a valid and reliable measuring instrument. The ITSM matrix is a measuring tool that has been internationally recognized in the ITSM and ITIL concepts. This research makes XYZ Higher Education the object of research. The basis of taking XYZ Higher Education is because these universities have used information technology in their business processes. However, problems are still found in the provision of IT services that have not met the expectations of IT Division and users. This can be seen from the percentage of reports on disruption that can be completed on time, only around 60% of the total reports submitted, and there is also a handling of reports of improper disturbances ranging from 19 - 29%. This is certainly a big concern that needs to be resolved by measuring the current level of IT services. After the measurement results using the ITSM matrix and guided by CMMI, it was found that the maturity level of the current IT service is still at level 1 (initial) where the service process runs ad-hoc and chaotic, and the success of the organization still comes from individual competence. This shows that XYZ universities, especially IT Division, need to improve IT services at a higher level in order to continue to improve IT services to users.